89 Geographical Variation of Emergency Hospital Admissions for Ambulatory Care Sensitive Conditions in Older Adults in the Republic of Ireland. (16th September 2019) - Walsh, Mary; Cronin, Sinéad; Boland, Fiona; Ebell, Mark; Wallace, Emma; Fahey, Tom
Abstract: Background: Hospitalisation for specific conditions considered to be `ambulatory-care sensitive' (ACS) could signify problems with primary or outpatient care access. The aims of this study are to quantify and explore potential causes for geographical variation across emergency hospital admissions for relevant ACS conditions in older adults in Ireland. Methods: The number of emergency hospital admissions among adults aged 65+ with a diagnosis of an ACS condition between 2012-2016 were extracted from Ireland's Hospital Inpatient Enquiry system according to condition, sex, age-group, residence area and year. Conditions included chronic obstructive pulmonary disease (COPD), congestive heart failure (CHF), diabetes complications, angina (excluding therapeutic procedures), pyelonephritis and urinary tract infections (UTI), dehydration and pneumonia. Age-sex standardised discharge rates (SDRs) were calculated for 21 areas. Systematic components of variance (SCV) quantified variation. Regression analyses were conducted between SDRs and year, unemployment rate, % urban population, General Practitioner (GP) supply, and % short emergency hospital stays. Results: In total, 147, 722 emergency hospital admissions (50 per 1, 000 eligible population; 49% male) were included. COPD was the most common condition (31%), followed by pneumonia (22%), pyelonephritis/UTI (21%) and CHF (16%). CHF showed low geographic variation (SCV=2-3). COPD, diabetes, pyelonephritis/UTI and pneumonia showed high variation (SCV=4-12). Angina and dehydration showed very high variation (SCV=12-50). In multivariable analysis, higher unemployment was associated with higher SDRs for COPD. Lower GP supply was associated with higher SDRs for CHF, diabetes and pneumonia. Rurality was associated with SDRs for angina. Conclusion: The rate of emergency admissions for ACS conditions studied is in line with research in the United States, although COPD and angina account for a higher proportion of admissions in our study. There is significant geographical variation in ACS admission rates among older adults in Ireland. Further research should explore local factors influencing emergency admission, particularly in socio-economically disadvantaged areas and those with lower GP supply.